Utilizing Gamification to Enhance Speaking Skills in Language Learning (Journal of Universal Science Research, 2024)
Gamification, or the use of game design aspects outside of games, has become a potent technique in language learning, especially for improving speaking abilities. This article explores how gamification affects language acquisition and highlights how it might help with speaking proficiency. It covers a range of gamified methods, the theoretical underpinnings of their efficacy, and useful implementation tactics for language learning. By incorporating gamification, teachers may design dynamic, stimulating, and engaging learning environments that help language learners become more proficient speakers.